Nucleic acids : - Bloomfield, Victor A. (University Science Books, 2000)
Nucleic Acids presents an up-to-date and comprehensive account of the structures and physical chemistry properties of nucleic acids, with special emphasis on biological function. With a targeted audience of 1)molecular biologists, 2)physical biochemists, and 3)physical chemists, the book has been carefully organized to reach three different audiences while requiring only introductory physical chemistry and molecular biology as prerequisites. Nucleic Acids will serve as a textbook in physical biochemistry and biophysical chemistry classes, as well as a supplemental text in courses on nucleic acid biochemistry or molecular biology, and as a personal reference for students and researchers in these fields.